PERCEPTIONS ON THE USE OF PLATFORM IN TEACHING AND LEARNING ENGLISH IN PANDEMIC ERA AT GRADE XII OF SMKN IN OKU - Andrea Dwima Septiana; Indawan Syahri; Mulyadi Mulyadi (Universitas PGRI Palembang, 2023)
The objective of this research was to determine the perceptions of teachers, students, and parents in using the Platform for Teaching and Learning English during the pandemic. This research is qualitative research with a qualitative description method. This research was carried out in SMK 1, 2, and 3 OKU with respondents being all English teachers, students, and parents of grade XII. Data collection techniques include observation techniques, questionnaires, and interviews. The results of the study show that the Platform (Google Classroom, Telegram, and Whatsapp) for teachers is very helpful as a medium for delivering materials, but assignments sent by students are sometimes still late, for students, as well, this media is helpful for them in learning during the pandemic, but sometimes accessing materials or collecting assignments is still difficult because the network is not stable and sometimes they don't have a quota, and for parents, this media is very helpful for their children to learn, but sometimes the network is not stable, so that it makes it difficult for them to access materials and collect their assignments as well as economic factors that make it difficult for them to buy internet quota.